2017
DOI: 10.1002/2017jc013288
|View full text |Cite
|
Sign up to set email alerts
|

Biogeochemical Impact of Snow Cover and Cyclonic Intrusions on the Winter Weddell Sea Ice Pack

Abstract: Sea ice is a dynamic biogeochemical reactor and a double interface actively interacting with both the atmosphere and the ocean. However, proper understanding of its annual impact on exchanges, and therefore potentially on the climate, notably suffer from the paucity of autumnal and winter data sets. Here we present the results of physical and biogeochemical investigations on winter Antarctic pack ice in the Weddell Sea (R. V. Polarstern AWECS cruise, June–August 2013) which are compared with those from two sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
40
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(44 citation statements)
references
References 102 publications
(128 reference statements)
4
40
0
Order By: Relevance
“…Following the same line, it is also likely that the high permeability and active brine cycling that developed in the relatively warm conditions of the AWECS study in the Western Weddell Sea might have homogenised the DMSP δ 34 S profiles towards oceanic values (Fig. 1a ), as observed for other biogeochemical variables during that study 30 .…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…Following the same line, it is also likely that the high permeability and active brine cycling that developed in the relatively warm conditions of the AWECS study in the Western Weddell Sea might have homogenised the DMSP δ 34 S profiles towards oceanic values (Fig. 1a ), as observed for other biogeochemical variables during that study 30 .…”
Section: Discussionsupporting
confidence: 54%
“…1 ). Pack ice was sampled at three different stations in the Western Weddell Sea (AWECS field study 30 ), and at four different stations in the central Ross Sea and Ross Sea marginal ice zone (PIPERS field study 31 ). One land-fast ice station was visited seven times during a year-round time series study in the McMurdo Sound, Ross Sea (YROSIAE field study 13 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies and reviews on Arctic fast ice have shown a seasonally changing influence of snow cover on ice algal bottom communities (Campbell et al, ; Lange et al, ; Mundy et al, ) and demonstrated how snow dynamics can alter the timing, duration, and magnitude of ice algal spring blooms (Leu et al, ). Recent Antarctic studies have highlighted the importance of snow loading for algal biomass accumulation in pack ice during winter and spring (Meiners et al, ; Tison, Schwegmann, et al, ), but the role of snow in driving Antarctic fast ice algal dynamics remains poorly understood. Snow depth data were available for 57.4% of the AFIAC sites and showed relative low variability, including a very high number of zero snow depth sites ( n = 299, 57.1% of all snow measurements).…”
Section: Discussionmentioning
confidence: 99%
“…In this case the ice algal community cannot reposition to the ice‐water interface through vertical migration (Aumack et al, ) and gets trapped in sea ice interior layers. On the other hand, in snow‐covered sea ice, surface flooding inducing warm and permeable conditions is an alternative mechanism for the establishment of internal Chl a maxima (e.g., Meiners et al, ; Tison, Schwegmann, et al, ).…”
Section: Discussionmentioning
confidence: 99%